The Rise and Demise of the Middle East Quest for Reforms, 2011–2017. (25th April 2017) - Aman, Mohammed M.
Abstract: Six years have passed since Arab masses in Tunisia, Egypt, Libya, Syria, Bahrain, and Yemen revolted against oppressive, corrupt, and autocratic regimes. These and lesser revolts in Morocco and Jordan — as well as muted ones in the oil producing Gulf States — shared common goals and themes: justice, dignity, economic, political, and social reforms (el‐Gingihy, 2017 ). The revolutionaries wanted to end government bloating and oppressive bureaucracies; and political and massive public corruption by the ruling classes; and instead, involve citizens in the participation in governance and policymaking. The oil‐rich countries were quick to shower their nationals with salary bonuses and more generous subsidies. The poorer Arab countries were quick to unleash their violent security forces on the masses in order to quell the uprisings using brute military force, including using poison gas in Syria, and operating mass killings of demonstrators at Rab'a Square in Cairo, Egypt. With the exception of Tunisia, the rest of the Arab countries reverted to oppressive regimes, or civil war chaos, as was the case in Libya and Yemen. The United States, which hailed the Arab uprisings during the reign of the Obama Administration, has changed course under the isolationist Trump Administration, which looks upon all Arabs and Muslim people and nations as potential supporters of what the current administration labels as Muslim terrorism. Along with an analysis of events in the region, this article also reviews the most recent books published which deal with the Arab revolts, and which include what lies ahead for the Arab world under the new rulers who replaced old regimes. It will also analyze the Arab countries' response to a Trump Administration that seems to adopt political isolationism, while at the same time, showing an obvious inclination for personal and national business involvement in the region, such as the recent opening of a Trump golf course in the United Arab Emirates, and the appointment of former MOBIL CEO Executive Rex Tillerson, who has strong business ties with Russia and the oil‐producing Gulf States.